2009
DOI: 10.1016/j.jmb.2008.10.068
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of PACT-Mediated PKR Activation in Tunicamycin-Induced Apoptosis

Abstract: Summary Cellular stresses such as disruption of calcium homeostasis, inhibition of protein glycosylation, and reduction of disulfide bonds result in accumulation of misfolded proteins in the endoplasmic reticulum (ER) and lead to cell death by apoptosis. Tunicamycin, which is an inhibitor of protein glycosylation, induces ER stress and apoptosis. In this study, we examined the involvement of double stranded (ds) RNA-activated protein kinase PKR and its protein activator PACT in tunicamycin-induced apoptosis. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 79 publications
3
50
0
Order By: Relevance
“…Our data suggest that hyperoxia-induced, PKR-mediated CHOP induction may be the mechanism by which hyperoxia augments cell death during ER stress. This is supported by the recent report that PKR activation by its endogenous activator PACT is required for maximal CHOP induction and cell death following tunicamycin-induced ER stress (36). We speculate that PKR activation and CHOP induction during O 2 therapy or in response to viral activation may promote further lung injury in diseases associated with epithelial ER stress, such as idiopathic pulmonary fibrosis (18,19) and smoking-related lung disease (14,16,17,22).…”
Section: Discussionsupporting
confidence: 70%
“…Our data suggest that hyperoxia-induced, PKR-mediated CHOP induction may be the mechanism by which hyperoxia augments cell death during ER stress. This is supported by the recent report that PKR activation by its endogenous activator PACT is required for maximal CHOP induction and cell death following tunicamycin-induced ER stress (36). We speculate that PKR activation and CHOP induction during O 2 therapy or in response to viral activation may promote further lung injury in diseases associated with epithelial ER stress, such as idiopathic pulmonary fibrosis (18,19) and smoking-related lung disease (14,16,17,22).…”
Section: Discussionsupporting
confidence: 70%
“…PKR, an eIF2α kinase, has recently emerged to be involved in ER stress-induced apoptosis by pharmacological ER inducers, thapsigargine and tunicamycin [20,31,32]. Lee et al found that activated PKR phosphorylated the eIF2α in a PERK-independent manner when HEK293A cells were treated with thapsigargine [20].…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of the PKR-like ER kinase (PERK) (Harding et al, 1999) has cast doubts on the involvement of PKR in the inhibition of protein synthesis caused by depletion of ER calcium stores. However, it has recently been established that PKR is activated in addition to PERK upon induction of ER stress by both thapsigargin and tunicamycin (Onuki et al, 2004;Lee et al, 2007;Singh et al, 2009).…”
Section: Introductionmentioning
confidence: 99%